Analisis Perbandingan Kelengkapan Rekam Medis Berdasarkan Metode Analisis Kuantitatif dengan Analisis Closed Medical Record Review di Rumah Sakit Kanker “Dharmais” - Mohammad Yusuf Setiawan; Lily Widjaja (Lembaga Penerbitan Universitas Esa Unggul, 2020)
AbstractMedical record is a file that contains records and documents about patient identity, examination, treatment, actions and other services that have been provided to patients. Medical records must be made immediately and completed after the patient receives the service. Examination of the completeness and quality of medical records using quantitative medical record analysis methods and Closed Medical Record Review. This study is intended to compare the completeness of the Medical Record Based on Quantitative Analysis Method with the Analysis of Closed Medical Record Review in